Методика определения координат силового центра алмазного долота - Бочковский, А.М. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2008)
The procedure of definition of coordinates of the power center of a diamond bit is developed. Calculations are executed and the actual arrangement of the power centers in used bits and drill heads is shown. New tools with the minimal deviation of the power center are created.